Induction of anti-tumour immune responses by overcoming tumour immune subversion - Dyck, Lydia (Trinity College (Dublin, Ireland). School of Biochemistry and Immunology, 2016)
Immunotherapy has considerable potential to improve disease outcome and survival of patients with cancer. Tumour eradication by the immune system is largely dependent on pro-inflammatory signals and effector cell infiltration at the tumour site. However, tumours can overcome effector immune responses, for example by the secretion of immunosuppressive molecules (TGF-3, retinoic acid (RA)), the recruitment of immunosuppressive cells (regulatory T (Treg) cells, myeloid-derived suppressor cells (MDSCs)) and the expression of immune checkpoint ligands (PD-L1, PD-L2). This project aimed to investigate approaches for activating anti-tumour immune responses, mechanisms of tumour-mediated immunosuppression and strategies to overcome immunosuppression.
Keywords: Biochemistry and Immunology, Ph.D.; PhD Trinity College Dublin, 2016